Numerical Study of Strengthened Spun Pile with Concrete Infill and Steel Jacket - Hugen, Stevany Lydia Jedidjah; Lase, Yuskar; Orientilize, Mulia (Rekayasa Sipil, 2024)
The confinements in a spun pile in Indonesia are below the minimum requirement mentioned in ASCE 7-16. Since Indonesia still adopts the linear elastic concept for foundation design, where the pile should be designed strongly without damage, the deficiency does not matter. However, enormous piles are required to keep it elastically under severe earthquakes. Hence, a transition to performance-based design (PBD) should be prepared since the seismic acceleration tends to increase. PBD requires sufficient transverse reinforcement to ensure flexural failure. Steel jacket is proposed to overcome the lack of confinements, particularly on the pile cap connection where the largest curvature occurs. Experimental and numerical studies have been conducted on a full-scale spun pile-to-pile cap connection with a steel jacket under cyclic loading. A monotonic pushover analysis with Opensees Navigator open-source software was performed for further study.